Effect of Fertilizer SP-36 and Green Tonic Fertliser Aplication on the Growth and Yield of Been Plant (Phaseolus vulgaris L) Perkasa Variety - Diki Kriswanto (Universitas 17 Agustus 1945 Samarinda, 2019)
The aim of this research is to know effect of SP-36 fertilizer and liquid green tonic fertilizer on the growth and yield of green been plants. The study was conducted from February 2017 until May 2017. The located of the recearch at Barong Tongkok Village, Subdistrict, Kutai Barat Recency. The receach design used Completely Randomized Design (RAL) in experimental factorial pattern 4 x 4 with 3 replications. Factor I : dosage of SP-36 fertilizer (P), consisting of 4 levels, namely : No SP-36 aplication or control (p0), SP-36 4 g /polibag (p1), SP-36 6 g/polibag (p2), and SP-36 8 g/polibag (p3). Factor II : Concentration of Green Tonic Fertilizer (G), consisting of 4 levels, namely : No green tonic fertilizer or control (g0), green tonic 2 ml / polibag (g1), green tonic 4 ml/polibag(g2) , and green tonic 6 ml/ polibag (g3).The result showed that SP-36 fertilizer treatment had no signfiicant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, long of fruit , ammount of fruit, and fruit weight per crop.The treatment of green tonic fertilizer had no significant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, length of fruit , number of fruit, and fruit weight per crop.The interaction treatment had no significant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, long of fruit , ammount of fruit, and fruit weight per crop.